Development of Benefit-risk Evaluation and Mitigation Systems in the Selection of Logistics Third Party Companies - Rusdiansyah, Ahmad; Pratama, Della Deswiana; Ibrahim, Muhammad Faisal (Jurnal Teknik Industri, 2020)
In this era, companies to transfer some of their logistical functions to third party logistics (3PL). In this study, a risk evaluation, and mitigation system at the initiation of collaboration with third-party logistics companies for agricultural chemical industry companies were developed. The basic model used in system development is House of Risk combined with SOAR methodology and scenario analysis. This system is used for consideration in decision making by evaluating and giving suggestions on the extent to which the use of 3PL is used to resolve company problems due to risk. The risk evaluation and mitigation system at the initiation of cooperation with a third-party logistics company in the agrochemical industry were successfully developed. The system consists of four processes (risk identification, risk analysis, risk evaluation, and risk response) compiled based on the ISO 31000: 2009 framework